2016
DOI: 10.4251/wjgo.v8.i11.757
|View full text |Cite
|
Sign up to set email alerts
|

Robotic rectal surgery: State of the art

Abstract: Laparoscopic rectal surgery has demonstrated its superiority over the open approach, however it still has some technical limitations that lead to the development of robotic platforms. Nevertheless the literature on this topic is rapidly expanding there is still no consensus about benefits of robotic rectal cancer surgery over the laparoscopic one. For this reason a review of all the literature examining robotic surgery for rectal cancer was performed. Two reviewers independently conducted a search of electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 60 publications
(406 reference statements)
5
37
1
2
Order By: Relevance
“…Основными причинами для кон-версии при мобилизации «сверху вниз» по данным исследования COLOR II являлись узкий таз, ожире-ние, ограниченная подвижность опухоли в тазу [6]. Роботическая техника при выполнении ТМЭ за счет известных преимуществ над несгибающимися лапа-роскопическими инструментами позволяет снизить час тоту конверсий у пациентов с ожирением, узким и длинным тазом, с опухолью в нижнеампулярном отделе [16]. Однако как для лапароскопической, так и для роботической операции сложным этапом явля-ется пересечение кишки после ее мобилизации.…”
Section: Discussionunclassified
“…Основными причинами для кон-версии при мобилизации «сверху вниз» по данным исследования COLOR II являлись узкий таз, ожире-ние, ограниченная подвижность опухоли в тазу [6]. Роботическая техника при выполнении ТМЭ за счет известных преимуществ над несгибающимися лапа-роскопическими инструментами позволяет снизить час тоту конверсий у пациентов с ожирением, узким и длинным тазом, с опухолью в нижнеампулярном отделе [16]. Однако как для лапароскопической, так и для роботической операции сложным этапом явля-ется пересечение кишки после ее мобилизации.…”
Section: Discussionunclassified
“…Postoperative hospital stay was also similar between robotic and conventional laparoscopic surgery according to meta‐analyses. However, some studies reported a shorter stay after robotic surgery, and others had the opposite finding .…”
Section: Short‐term Postoperative Outcomesmentioning
confidence: 97%
“…Postoperative complications are important for discussing the safety of robotic surgery. Meta‐analyses showed that there was no significant difference in the frequency of overall complications between robotic and conventional laparoscopic surgery . For example, anastomotic leakage, the most frequent complication, occurred in 2.4%–11.2% of cases that underwent conventional laparoscopic rectal surgery and in 1.8%–13.5% that underwent robotic surgery .…”
Section: Short‐term Postoperative Outcomesmentioning
confidence: 99%
See 2 more Smart Citations